Correlation calculation decrypting for BSS-based image cryptosystem - LIN Qiu-hua; DANG Jie; YIN Fu-liang (Tongxin xuebao)
For a blind source separation （BSS） based method for encrypting multiple images, the multiple decrypted im- ages by BSS may have changed order and reversed pixel values. In addition, decorrelation preprocessing must be per- formed prior to decryption of strongly correlated images. To solve the two problems, a novel method for image decryp- tion was proposed based on correlation calculation since the key images are known for legal users and are independent of the original images. Specifically, the correlation matrix between the encrypted images and the key images was calculated according to the encryption equation, the decrypted images are then obtained by ignoring the smaller correlation matrix between the original images and the key images. The results of computer simulations and performance analyses demon- strate that the proposed method can provide much higher quality and much faster speed compared to the BSS decryption, and also can directly decrypt varied images.